Transforming non-conventional yeasts into key players in biotechnology: advances in synthetic biology applications - Moon, Soo Young; An, Nan-Yeong; Lee, Ju Young (Frontiers in Microbiology, 2025)
Non-conventional yeasts exhibit exceptional genetic and functional diversity, serving as a largely untapped repertoire for biotechnological applications. Beyond the conventional yeast Saccharomyces cerevisiae, non-conventional yeasts are naturally more multifaceted, possessing the ability to utilize renewable and low-cost carbon sources while exhibiting robust physiology under challenging conditions. However, their vast potential remains largely unexplored, encompassing both challenges and opportunities for biotechnological advancements. Over the past decade, technological advancements in synthetic biology have unlocked new opportunities to harness their potential and overcome inherent limitations, enabling the full exploitation of their advantages across a broad spectrum of applications. In this review, we highlight recent advances in the synthetic biology of non-conventional yeasts, focusing on the development of new genetic building blocks (e.g., promoters and terminators), genome editing tools, and metabolic pathway engineering. Through these technologies, non-conventional yeasts are poised to emerge as pivotal next-generation workhorses tailored for specific applications in sustainable biomanufacturing, accelerating the transition to a bio-based economy.